Penghindaran Pajak, Menguntungkan atau Merugikan? - Lutfi Madani; Memen Kustiawan; Ida Farida Adi Prawira (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
Taxes are an important aspect of state revenue. The taxation sector contributes the most compared to sources of state revenue. One of the tax objects in Indonesia is corporate or corporate taxpayers. So far, the company has contributed to tax revenue for the State. However, there are still no companies that voluntarily pay the tax burden, because it effects company's profit rate. This encourages companies to decrease their tax fees by implementing tax avoidance. Tax avoidance itself can provide its own advantages and disadvantages for the company. The method used in this research is Systematic Literature Review (SLR), where the authors make observations of articles published within the last 10 years (2014-2022). This study reveals that tax avoidance can provide both positive and negative benefits for companies.